Analyzing the impact of spatial centrality and courtyard diversity on tourist attractions in the walled city of Lefkoşa - Mustafa Aziz Amen; Farhan Abdullah Ali (PLoS ONE, 2025)
The Walled City of Lefkoşa faces the dual challenge of preserving its historic urban fabric while addressing the evolving demands of modern tourism. A key problem lies in understanding the interplay between spatial centrality within the urban street network and the diversity of courtyard activities influencing tourist attraction and engagement. This study hypothesizes that while spatial centrality plays a significant role in guiding tourist movement and enhancing visibility, the diversity and adaptability of courtyard spaces have a greater impact on enriching visitor experiences. To test this hypothesis, the research employs a mixed-methods approach, combining quantitative and qualitative analyses. PageRank and Straightness centrality analysis are used to model the street network and assess the prominence and connectivity of key streets. Simultaneously, field observations and visitor data are integrated into GIS-based mapping tools to visualize spatial patterns of movement and activity. The findings reveal that courtyards hosting diverse and adaptable activities significantly enhance tourist engagement, even in less central locations. In contrast, areas with high centrality but limited courtyard adaptability struggle to sustain prolonged visitor interactions. These results underscore the importance of integrating spatial centrality with thoughtfully designed, multifunctional courtyard spaces in urban planning strategies. This research offers actionable insights for urban planners, architects, and heritage managers, advocating for a balanced approach that preserves the historic character of urban areas while meeting the dynamic needs of contemporary tourism.